Kasus Bullying di Lingkungan Sekolah: Dampak Serta Penanganannya - Elsya Derma Putri (Keguruan, 2022)
Bullying cases that arise can be influenced by a variety of circumstances. Bullying has an adverse effect on both the victim and the bullied. For this reason, students who have been bullied need to be handled. The purpose of this study is to identify the contributing variables and the forms of care provided to bullied kids. To precisely and methodically characterize the facts that transpired throughout the inquiry, descriptive qualitative research was performed. Interviews, observation, and documentation were the data gathering techniques employed. The outcomes of data processing show that counseling techniques are used to handle bullying victims who are students. The steps are recognition, diagnosis, prognosis, therapy, and follow-up. Therefore, in order to lessen the conduct of pupils who are bullied, counselors must increase their ingenuity in dealing with such students.